THE EFFECT OF DEMOTION, MUTATION AND POSITION PROMOTION ON EMPLOYEE MOTIVATION OF BANK INDONESIA REPRESENTATIVE OFFICE - Suhelmi Helia; Riki Chandra; Yoki oktorizka; Syamsuddin Syamsuddin; Nirpa srihayu (SEAN Institute, 2023)
This study aims to determine the effect of demotions, transfers and promotions on the work motivation of Bank Indonesia West Sumatra employees. The method used in this research is quantitative research with a descriptive approach. The population in this study were all employees of Bank Indonesia West Sumatra. The sample used was 68 people using total sampling theory. The data analysis technique is multiple linear regression. The results showed that: (1) Demotion had a negative and significant effect on the work motivation of West Sumatra Bank Indonesia employees. (2) Mutations have a negative and significant effect on the work motivation of West Sumatra Bank Indonesia employees. (3) Promotion has a positive and significant effect on the work motivation of West Sumatra Bank Indonesia employees. (4) Demotions, transfers and promotions simultaneously have a significant effect on the work motivation of Bank Indonesia West Sumatra employees.